The Synergy Effect of Azadirachtin and Minor Components of Neem Seed Oil on Antifeedant Activity of Spodoptera litura - Arief Heru Prianto; NFN Budiawan; Yoki Yulizar; Partomuan Simanjuntak (Buletin Penelitian Tanaman Rempah dan Obat, 2019)
Azadirachtin in neem oil (Azadirachta indica A.Juss) might have potential synergism effect with a minor compound in the neem oil as an antifeedant. This study aimed to determine the content of minor components that have the most significant contribution to the effect of synergy with the main component (azadirachtin) in antifeedant activity against Spodoptera litura. Neem oil was fractionated with n-hexane, ethyl acetate, and water. The antifeedant activity of three neem oil fractions was evaluated using the 4th instar of S. litura larvae. The bioassay was conducted using the choice leaf disc test with 2.5; 5; 10; and 20 % (v/v) concentrations of each fraction. The concentration of the fractions showed equal azadirachtin content, hence the antifeedant activity represented the effect of the minor component in the fraction. The best activity was shown by water fraction (84-100 %). Probit analysis of the antifeedant activity of all fractions showed that water fraction has the best effective inhibitory (EI50) at 1.0 %.  The minor component in the water fraction was dominated by phenol compounds (48.5 %) which were suspected to synergize with the main component (azadirachtin) in increasing the antifeedant activity on S. litura. These results indicated the phenol compound in this fraction has the role in increasing azadirachtin antifeedant activity against S. litura.